A Ti2CT based on ferrous ion modification x Preparation method and application of flexible sensor based on carrageenan-polyacrylamide composite hydrogel

CN116751373BActive Publication Date: 2026-10-23NANJING TECH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310572996.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2026-10-23
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

其次,由于声子在水凝胶内部的高分子链中散射损失较多,导致水凝胶材料的热导率较低,水凝胶材料对温度的响应较低

Benefits of technology

[0026] Carrageenan-polyacrylamide hydrogel, as an ion conductor, possesses a three-dimensional network structure, providing sufficient ion channels and exhibiting certain mechanical strength, making it suitable for the fabrication of flexible temperature sensors. Ti2CT x The electrical and thermal conductivity of the material was improved by incorporating ferrous ions. The doping of ferrous ions increased the ion concentration in the composite hydrogel, further enhancing the temperature response of the carrageenan-polyacrylamide hydrogel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116751373B_ABST
    Figure CN116751373B_ABST
Patent Text Reader

Abstract

This invention relates to a Ti2CT based on ferrous ion modification. x The preparation method and application of a flexible sensor based on carrageenan-polyacrylamide composite hydrogel belong to the field of functional material preparation technology. (Ti2CT) x A composite material was created by combining carrageenan with polyacrylamide, followed by salt infiltration to modify the composite with ferrous ions. This improved the composite's resistance to dryness and freezing, as well as its temperature response. A flexible temperature sensor was then fabricated using this composite material and a flexible interdigitated electrode. The excellent mechanical properties and good ionic conductivity of carrageenan-polyacrylamide hydrogel make it suitable for the fabrication of flexible temperature sensors, specifically Ti2CT. x While improving the conductivity of the material, its large specific surface area provides more paths for the propagation of phonons in the composite material, thereby improving the temperature response capability of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a Ti2CT based on ferrous ion modification. x The preparation method and application of flexible sensors based on carrageenan-polyacrylamide composite hydrogels belong to the field of functional two-dimensional / three-dimensional hybrid material preparation technology. Background Technology

[0002] Human body temperature changes dynamically and in real time reflect a person's physiological condition. Abnormal physiological conditions such as fever, colds, and low blood flow can all be detected through changes in body temperature. Therefore, accurate and real-time detection of human body temperature is crucial for monitoring health and maintaining thermal homeostasis. Currently, many temperature sensors have been developed that detect changes in physical parameters to measure body temperature. Mercury thermometers and infrared thermometers are widely used in daily life. While mercury thermometers can sensitively detect human body temperature, they require a long detection time and are easily damaged. Infrared thermometers, although highly accurate and fast-responding, are expensive. To meet the demand for low cost, fast response, accurate temperature measurement, and real-time monitoring of human body temperature, flexible wearable temperature sensors have been developed. In the manufacturing of flexible wearable temperature sensors, hydrogels are widely used as the substrate material due to their good biocompatibility and excellent mechanical properties. However, current hydrogel-based flexible temperature sensors still suffer from problems such as poor repeatability and poor linearity.

[0003] To address the aforementioned issues with hydrogel sensors, the stability of the hydrogel material must first be improved. Because hydrogels contain a large amount of water, the sensor becomes inactive in sub-zero temperatures due to water freezing; in dry environments, rapid water loss causes the three-dimensional structure to collapse, leading to sensor failure. Therefore, improving the anti-drying and anti-freezing properties of hydrogel materials is crucial for ensuring the long-term stable operation of hydrogel-based sensors. Currently, solvent replacement and salt infiltration are common methods for preparing anti-drying and anti-freezing hydrogels. Salt infiltration is widely used due to its simplicity and good biocompatibility. Furthermore, salt infiltration can introduce additional ions into the hydrogel, improving its electrical conductivity. Secondly, due to significant phonon scattering loss within the polymer chains of the hydrogel, the thermal conductivity of the hydrogel material is low, resulting in a low temperature response. To improve the temperature-sensitive response of hydrogel-based sensors, high thermal conductivity carbon materials such as graphene, carbon nanotubes, and MXene are used as fillers in composites with the hydrogel. This not only improves the thermal conductivity of the hydrogel but also compensates for its poor electrical conductivity. Among them, MXene is widely used as a filler to improve the thermal conductivity and electrical conductivity of hydrogel materials due to its large specific surface area, abundant surface functional groups and good mechanical properties. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention proposes a Ti2CT based on ferrous ion modification. x Preparation method and application of flexible sensor based on carrageenan-polyacrylamide composite hydrogel. (Ti2CT) x A composite material was created by combining carrageenan-polyacrylamide hydrogel, followed by modification of the composite hydrogel with ferrous ions to improve the material's resistance to drying and freezing, as well as its temperature response. This composite material was then combined with flexible interdigitated metal electrodes to fabricate a flexible temperature sensor. This invention presents a ferrous ion-modified Ti2CT. x The flexible sensor made of carrageenan-polyacrylamide composite hydrogel exhibits fast temperature sensing response, high sensitivity, and good repeatability.

[0005] To solve the above technical problems, the proposed technical solution is: a ferrous ion-modified Ti2CT x The preparation method of carrageenan-polyacrylamide composite hydrogel material includes the following steps:

[0006] (1) Carrageenan, acrylamide, N,N′-methylenebisacrylamide and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone were dispersed and dissolved in deionized water, and heated and stirred until the solid was completely dissolved to obtain a carrageenan-polyacrylamide (CA-PAM) hydrogel prepolymer.

[0007] (2) Titanium carbide Ti2CT x The aqueous solution of nanosheets was added to the carrageenan-polyacrylamide hydrogel prepolymer solution prepared in step (1), and stirred until Ti2CT was reached. x The aqueous solution was mixed evenly with the carrageenan-polyacrylamide hydrogel prepolymer to obtain Ti2CT. x Carrageenan

[0008] - Polyacrylamide (Ti2CT) x / CA-PAM) composite hydrogel prepolymer;

[0009] (3) Transfer the composite hydrogel prepolymer obtained in step (2) into a petri dish and refrigerate it at 4°C until it solidifies;

[0010] (4) Ti2CT was prepared by irradiating the solid obtained in step (3) with ultraviolet light. x / Carrageenan-polyacrylamide composite hydrogel;

[0011] (5) The Ti2CT obtained in step (4) x Ferrous-modified Ti2CT was prepared by immersing carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferrous chloride solution. x / Carrageenan-Polyacrylamide Fe2+ / Ti2CT x / CA-PAM composite hydrogel material.

[0012] Preferably, in step (1), the mass ratio of carrageenan, acrylamide, N,N′-methylenebisacrylamide and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone is 80.2:16.05:3.6:0.15, the stirring rate is 1000 rpm, the heating temperature is 95°C, and the heating time is 2 h.

[0013] In step (2), Ti2CT x The aqueous solution concentration was 15 mg / mL, the volume ratio of the aqueous solution to the hydrogel prepolymer was 9:1, the stirring speed was 1000 rpm, and the stirring time was 10 min.

[0014] In step (4), the wavelength of the ultraviolet lamp is 365nm and the illumination time is 1h;

[0015] In step (5), the concentration of ferrous chloride is 4 mol / L and the soaking time is 2 h.

[0016] Preferably, (1) 0.6g LiF is mixed evenly with 6mL hydrochloric acid, and then 0.2g of commercial Ti2AlC (transition metal carbonitride) is added. The mixture is stirred at 40℃ for 24h. The product is centrifuged to obtain a precipitate. The precipitate is dispersed in deionized water to remove O2 and repeatedly shaken and washed until the pH of the dispersion is between 6 and 7. Ti2CT with a thinner lamellar structure can be obtained. x Nanosheets;

[0017] (2) Add 1.12g of carrageenan, 0.224g of acrylamide, 0.002g of N,N′-methylenebisacrylamide and 0.05g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone to 45mL of deionized water and stir at 1000rpm and 95℃ for 2 hours. Then add 5mL of Ti2CT from step (1) with a concentration of 15mg / mL. x An aqueous solution of nanosheets was added to the above mixed solution, and the mixture was stirred at 1000 rpm for 10 minutes to obtain Ti2CT. x A prepolymer solution for carrageenan-polyacrylamide composite hydrogel was prepared; after storing the petri dish containing the prepolymer solution at 4°C for one hour, the sample was irradiated with ultraviolet light for one hour to obtain Ti2CT. x / Carrageenan-polyacrylamide composite hydrogel;

[0018] (3) The Ti2CT in step (2) xAfter immersing the carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferrous chloride solution for 2 hours, ferrous ion-modified Ti2CT can be obtained. x / Carrageenan-polyacrylamide composite hydrogel.

[0019] To solve the above-mentioned technical problems, the proposed technical solution is: any of the ferrous ion-modified Ti2CTs described above. x A composite hydrogel prepared by a method for preparing carrageenan-polyacrylamide composite hydrogels.

[0020] To solve the above technical problems, the proposed technical solution is as follows: the ferrous ion-modified Ti2CT... x A method for preparing flexible sensors using carrageenan-polyacrylamide composite hydrogels, employing spin coating to coat the prepared Ti2CT... x A flexible temperature sensor was fabricated by spin-coating a prepolymer solution of carrageenan-polyacrylamide composite hydrogel onto a flexible interdigitated electrode. Except for the electrodes at both ends which were exposed, the other part was covered by the prepolymer solution. The flexible interdigitated electrode coated with the prepolymer solution was stored at 4°C for 20 minutes, then irradiated with ultraviolet light for 20 minutes, and finally immersed in a 4M FeCl2 solution for 10 minutes.

[0021] To address the aforementioned technical problems, another proposed technical solution is: the preparation of ferrous ion-modified Ti2CT. x Flexible sensor prepared from carrageenan-polyacrylamide composite hydrogel.

[0022] To address the aforementioned technical problems, another proposed technical solution is: the flexible sensor is used for temperature detection.

[0023] Preferably, the two electrodes of the flexible temperature sensor are connected to the data acquisition unit via wires. The flexible temperature sensor is placed on a semiconductor hot and cold stage, and the data acquisition unit records the temperature sensor's response to temperature changes.

[0024] Preferably, it can be used for detecting human body temperature.

[0025] The beneficial effects of this invention are:

[0026] Carrageenan-polyacrylamide hydrogel, as an ion conductor, possesses a three-dimensional network structure, providing sufficient ion channels and exhibiting certain mechanical strength, making it suitable for the fabrication of flexible temperature sensors. Ti2CT x The electrical and thermal conductivity of the material was improved by incorporating ferrous ions. The doping of ferrous ions increased the ion concentration in the composite hydrogel, further enhancing the temperature response of the carrageenan-polyacrylamide hydrogel.

[0027] 1. The ferrous ion-modified Ti2CT of the present inventionx Carrageenan-polyacrylamide composite hydrogels improve the drought resistance, freeze resistance, thermosensitivity, and conductivity of sensing materials. Ferrous ions and Ti2CT... x The combination with carrageenan-polyacrylamide hydrogel improved the ion concentration and thermal conductivity of the material, thereby enhancing the material's temperature sensing response.

[0028] 2. The ferrous ion-modified Ti2CT prepared in this invention x The carrageenan-polyacrylamide composite hydrogel exhibits excellent anti-drying and anti-freezing properties. Compared to the composite hydrogel without ferrous ion modification, it can still retain 60% of its moisture after being exposed to room temperature for three days.

[0029] 3. The ferrous ion-modified Ti2CT prepared in this invention x The flexible sensor made of carrageenan-polyacrylamide composite hydrogel can be stored at room temperature and responds to temperature sensing.

[0030] 4. The ferrous ion-modified Ti2CT prepared in this invention x The flexible sensor made of carrageenan-polyacrylamide composite hydrogel exhibits fast temperature sensing response, high sensitivity, and good repeatability.

[0031] 5. The ferrous ion-modified Ti2CT prepared in this invention x Carrageenan-polyacrylamide composite hydrogel materials can be fabricated into flexible wearable sensors to achieve rapid and accurate detection of human body temperature.

[0032] 6. Ferrous ion-modified Ti2CT prepared in Examples 2 and 3 x The analysis was performed on the carrageenan-polyacrylamide composite hydrogel, such as... Figure 5 As shown, under the same soaking time, the anti-drying properties of the composite hydrogel gradually improved with increasing ferrous chloride concentration. The hydrogel that had been soaked in 4M FeCl2...

[0033] The composite hydrogel of the solution still retains 60% of its water content after three days. For example... Figure 6 As shown, the peak value on the DSC curve that decreases with temperature reflects the solidification point of the composite hydrogel. The peak value of the DSC curve gradually decreases with increasing FeCl2 solution concentration. The composite hydrogel soaked in 4M FeCl2 shows no obvious peak value in the -80℃ to 0℃ range, demonstrating that the composite hydrogel soaked in 4M FeCl2 solution has good anti-drying and anti-freezing properties.

[0034] 7. Ti2CT x After immersing the carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferric chloride solution for 2 hours, Ti2CT modified with different iron ion contents can be obtained.x / Carrageenan-polyacrylamide composite hydrogel. For example... Figure 7 As shown, under the same soaking time, the anti-drying properties of the composite hydrogel gradually improved with the increase of ferric chloride concentration. The composite hydrogel soaked in 4M FeCl3 solution could still retain 40% water after three days. However, compared with the ferrous chloride-modified Ti2CT prepared in Examples 2 and 3, the anti-drying properties of the composite hydrogel gradually improved with the increase of ferric chloride concentration. x / Carrageenan-polyacrylamide composite hydrogel, the iron-doped composite hydrogel has poor anti-drying properties.

[0035] 8. For example Figure 13 As shown, due to the large baseline resistance of CA-PAM, its resistance change caused by temperature variations is not significant, making it unsuitable for fabrication as a temperature sensor. Furthermore, the CA-PAM hydrogel also exhibits a low temperature response, largely due to the scattering and loss of phonons during transport between polymer chains, resulting in low thermal conductivity. In this invention, Ti2CT, with its higher thermal conductivity, was selected. x Nanosheets (2.241 W·m K) -1 Combining it with hydrogel improves the thermal conductivity of the material. For example... Figure 15 As shown, compared with Ti2CT x The thermal conductivity of CA-PAM after composite formation is 0.598 W·(m K). -1 Increased to 0.622 W·(m K) -1 Ti2CT x The thermal conductivity of the CA-PAM hydrogel is higher than that of Liu et al. (Liu, H., et al., Nat. Commun., 2022, 13, 3420) in Ti3CT. x As a filler material, the thermal conductivity of the prepared composite hydrogel is 0.39 W·(m K). -1 ).

[0036] 9. The excellent mechanical properties and good ionic conductivity of carrageenan-polyacrylamide hydrogel make it suitable for the fabrication of flexible temperature sensors, such as Ti2CT. x While improving the material's electrical conductivity, its large specific surface area provides more pathways for phonon propagation within the composite material, thereby enhancing its temperature response. Furthermore, the introduction of ferrous ions increases the hydrogen ion concentration in the composite, further improving the temperature response of the composite hydrogel material. Attached Figure Description

[0037] The present invention will be further described below with reference to the accompanying drawings.

[0038] Figure 1 It is Ti2CT xSEM image of nanosheets.

[0039] Figure 2 It is Ti2CT x / SEM image of carrageenan-polyacrylamide hydrogel.

[0040] Figure 3 It is Ti2CT x / SEM image of carrageenan-polyacrylamide hydrogel.

[0041] Figure 4 It is Ti2CT x Mapping diagram of carrageenan-polyacrylamide hydrogel.

[0042] Figure 5 It is ferrous ion modified Ti2CT x Mapping diagram of carrageenan-polyacrylamide hydrogel.

[0043] Figure 6 It is ferrous ion modified Ti2CT x Comparison of water loss in carrageenan-polyacrylamide hydrogels.

[0044] Figure 7 It is ferrous ion modified Ti2CT x / DSC curve of carrageenan-polyacrylamide hydrogel.

[0045] Figure 8 Ferrous ion-modified Ti2CT was prepared on a flexible gold interdigitated electrode. x / A physical image of carrageenan-polyacrylamide hydrogel.

[0046] Figure 9 It is ferrous ion modified Ti2CT x / Graph showing the change in electrical resistance of carrageenan-polyacrylamide hydrogel to different temperature changes.

[0047] Figure 10 It is ferrous ion modified Ti2CT x / Graph showing the change in electrical resistance of carrageenan-polyacrylamide hydrogel to different temperature changes.

[0048] Figure 11 It is ferrous ion modified Ti2CT x / The change in electrical resistance of carrageenan-polyacrylamide hydrogel with a temperature gradient of 0.1℃.

[0049] Figure 12 It is ferrous ion modified Ti2CT x / Response values ​​of carrageenan-polyacrylamide hydrogel heated to 40°C at different heating rates.

[0050] Figure 13 It is the baseline resistance of carrageenan-polyacrylamide hydrogel. Figure 14 It is ferrous ion modified Ti2CT x Repeatability of the carrageenan-polyacrylamide hydrogel temperature sensor.

[0051] Figure 15 It is carrageenan-polyacrylamide hydrogel and Ti2CT x / Thermal conductivity of carrageenan-polyacrylamide hydrogel.

[0052] Figure 16 It is ferrous ion modified Ti2CT x / Carrageenan-polyacrylamide hydrogel temperature sensor detects changes in resistance response when the human body is at different temperatures. Detailed Implementation

[0053] To better understand the present invention, the technical solution of the present invention will be specifically described below with reference to the accompanying drawings and specific embodiments.

[0054] Example 1: Ti2CT x Preparation of nanosheets

[0055] 0.6 g of LiF was mixed thoroughly with 6 mL of hydrochloric acid, and then 0.2 g of commercial transition metal carbonitride Ti₂AlC was added. The mixture was stirred at 40 °C for 24 h. The product was centrifuged to obtain a precipitate. The precipitate was dispersed in deionized water (O₂ removed) and repeatedly shaken and washed until the pH of the dispersion was between 6 and 7. Ti₂CT with a relatively thin lamellar structure was obtained. x Nanosheets. For the Ti2CT prepared in Example 1 x The nanosheets were characterized, and the SEM images of the nanosheets are shown below. Figure 1 As shown.

[0056] Example 2: Ti2CT x Preparation method of carrageenan-polyacrylamide hydrogel

[0057] 1.12 g of carrageenan, 0.224 g of acrylamide, 0.002 g of N,N′-methylenebisacrylamide, and 0.05 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone were added to 45 mL of deionized water and stirred at 1000 rpm and 95 °C for 2 hours. Then, 5 mL of Ti₂CT at a concentration of 15 mg / mL was added. x An aqueous solution was added to the above mixed solution, and stirring was continued at 1000 rpm for 10 minutes to obtain Ti2CT. xA prepolymer solution for carrageenan-polyacrylamide composite hydrogels was prepared. After storing the petri dish containing the prepolymer solution at 4°C for one hour, the sample was irradiated with ultraviolet light for one hour to obtain Ti2CT. x / Carrageenan-polyacrylamide composite hydrogel.

[0058] The Ti2CT prepared in Example (1) x The carrageenan-polyacrylamide composite hydrogel was characterized, and the SEM images of the composite hydrogel are shown below. Figure 2 As shown, it exhibits a three-dimensional porous mesh structure. Figure 3 As shown in the image, magnifying the pore walls of the composite hydrogel reveals a layered structure with gaps of 4–20 nm between the layers. Figure 4 As shown, the distribution of Ti, O, C, and N elements was acquired using EDS surface scanning. The uniform distribution of the four elements in the material demonstrates the successful fabrication of Ti2CT. x / Carrageenan-polyacrylamide composite hydrogel.

[0059] Example 3: Ferrous ion modified Ti2CT x Preparation method of carrageenan-polyacrylamide composite hydrogel

[0060] Ti2CT x After immersing the carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferrous chloride solution for 2 hours, ferrous ion-modified Ti2CT can be obtained. x / Carrageenan-polyacrylamide composite hydrogel.

[0061] The composite hydrogel obtained in Example 2 was analyzed. For example... Figure 5 As shown, the distribution of four elements, Fe, Ti, F, and Cl, was collected using EDS surface scanning. It can be seen that Fe is uniformly distributed in the material, proving that Fe... 2+ / Ti2CT x Successful preparation of carrageenan-polyacrylamide composite hydrogel.

[0062] Example 4: Ferrous ion modified Ti2CT x Preparation method of carrageenan-polyacrylamide composite hydrogel

[0063] Ti2CT x After immersing carrageenan-polyacrylamide composite hydrogels in 1 mol / L or 2 mol / L ferrous chloride solutions for 2 hours, Ti2CT modified with different ferrous ion contents can be obtained. x / Carrageenan-polyacrylamide composite hydrogel.

[0064] Ferrous ion-modified Ti2CT prepared in Examples 3 and 4x The analysis was performed on the carrageenan-polyacrylamide composite hydrogel, such as... Figure 6 As shown, under the same soaking time, the anti-drying properties of the composite hydrogel gradually improved with increasing ferrous chloride concentration. The hydrogel that had been soaked in 4M FeCl2...

[0065] The composite hydrogel of the solution still retains 60% of its water content after three days. For example... Figure 7 As shown, the peak value on the DSC curve that decreases with temperature reflects the solidification point of the composite hydrogel. The peak value of the DSC curve gradually decreases with increasing FeCl2 solution concentration. The composite hydrogel soaked in 4M FeCl2 shows no obvious peak value in the -80℃ to 0℃ range, demonstrating that the composite hydrogel soaked in 4M FeCl2 solution has good anti-drying and anti-freezing properties.

[0066] Example 5: Iron-modified Ti2CT x Preparation method of carrageenan-polyacrylamide composite hydrogel

[0067] Ti2CT x After immersing the carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferric chloride solution for 2 hours, Ti2CT modified with different iron ion contents can be obtained. x / Carrageenan-polyacrylamide composite hydrogel. For example... Figure 7 As shown, under the same soaking time, the anti-drying properties of the composite hydrogel gradually improved with the increase of ferric chloride concentration. The composite hydrogel soaked in 4M FeCl3 solution could still retain 40% water after three days. However, compared with the ferrous chloride-modified Ti2CT prepared in Examples 3 and 4, the anti-drying properties of the composite hydrogel gradually improved with the increase of ferric chloride concentration. x / Carrageenan-polyacrylamide composite hydrogel, the iron-doped composite hydrogel has poor anti-drying properties.

[0068] Example 6: Ti2CT based on ferrous ion modification x Preparation method of flexible sensor of carrageenan-polyacrylamide composite hydrogel

[0069] Using spin coating, 80 μL of Ti2CT prepared in Example 1 was processed. x A prepolymer solution of carrageenan-polyacrylamide composite hydrogel was spin-coated onto a flexible interdigitated electrode. Except for the exposed electrodes at both ends, the remaining portion was covered by the prepolymer solution. The prepolymer-coated flexible interdigitated electrode was then stored at 4°C for 20 minutes and subsequently irradiated with ultraviolet light for 20 minutes. After immersing the electrode in a 4M FeCl2 solution for ten minutes, a flexible temperature sensor was obtained.

[0070] Figure 8 Fe prepared on gold interdigitated electrodes 2+ / Ti2CT x / A physical image of a carrageenan-polyacrylamide hydrogel temperature sensor. The dimensions of the flexible gold interdigitated electrodes are: length 1cm, width 1cm, and spacing 0.05mm.

[0071] Example 7: Temperature Sensing Response of Flexible Temperature Sensor

[0072] (1) The two electrodes of the flexible temperature sensor are connected to the data acquisition unit through wires. The flexible temperature sensor is placed on the semiconductor hot and cold stage, and the data acquisition unit records the response of the temperature sensor to temperature changes.

[0073] (2) When the temperature of the hot and cold stage is 20℃, record the resistance of the sensor as R0.

[0074] (3) Record the resistance of the sensor at a specific temperature, with a temperature gradient of 5℃, the temperature rises from 20℃ to 60℃ and with a temperature gradient of 5℃, the temperature drops from 20℃ to -10℃.

[0075] (4) The measured resistance response is recorded as ΔR / R0, where R0 is the baseline resistance at 20℃, and ΔR is the resistance change relative to the baseline resistance after the temperature change.

[0076] The above test results were analyzed, such as... Figure 9 , 10 As shown, Fe 2+ / Ti2CT x The graph shows the resistance response of a carrageenan-polyacrylamide composite hydrogel to different temperatures. The temperature sensor has a detection range of -10 to 60°C. The resistance decreases as the temperature increases and increases as the temperature decreases. Figure 11 As shown, the sensitivity of the composite hydrogel sensor was tested between 23.6 and 24.2℃ with a temperature gradient of 0.1℃. For every 0.1℃ change in temperature, the sensor's response value changed by 0.1%, which is consistent with the calculated results, demonstrating that the composite hydrogel sensor has high sensitivity (TCR = 1.07 ± 0.013% / ℃). Figure 12 As shown, the temperature response of the composite hydrogel temperature sensor was tested at different heating rates (5 min / ℃, 15 min / ℃, 20 min / ℃). It can be seen that the sensor's temperature response is not affected by the heating rate. Figure 14 This demonstrates that the material has good repeatability.

[0077] like Figure 13As shown, due to the large baseline resistance of CA-PAM, its resistance change caused by temperature variations is not significant, making it unsuitable for fabrication as a temperature sensor. Furthermore, the CA-PAM hydrogel also exhibits a low temperature response, largely due to the scattering and loss of phonons during transport between polymer chains, resulting in low thermal conductivity. In this invention, Ti2CT, with its higher thermal conductivity, was selected. x Nanosheets (2.241 W·m K) -1 Combining it with hydrogel improves the thermal conductivity of the material. For example... Figure 15 As shown, compared with Ti2CT x The thermal conductivity of CA-PAM after composite formation is 0.598 W·(m K). -1 Increased to 0.622 W·(m K) -1 Ti2CT x The thermal conductivity of the CA-PAM hydrogel is higher than that of Liu et al. (Liu, H., et al., Nat. Commun., 2022, 13, 3420) using Ti3CT. x As a filler material, the thermal conductivity of the prepared composite hydrogel is 0.39 W·(m K). -1 ).

[0078] Example 8: Detection of human body temperature using a flexible temperature sensor

[0079] (1) The two electrodes of the flexible temperature sensor are connected to the data acquisition unit through wires. The flexible temperature sensor is placed on the semiconductor hot and cold stage, and the data acquisition unit records the response of the temperature sensor to temperature changes.

[0080] (2) When the temperature of the hot and cold stage is 20℃, record the resistance of the sensor as R0.

[0081] (3) Record the resistance when the sensor is attached to the volunteer's forehead.

[0082] (4) The measured resistance response is recorded as ΔR / R0, where R0 is the baseline resistance at 20℃, and ΔR is the resistance change relative to the baseline resistance after the temperature change.

[0083] Analyzing the above results, such as... Figure 16 As shown, the composite hydrogel temperature sensor can distinguish the body temperatures of two volunteers with very small differences (the temperature difference is only 0.4℃).

[0084] The present invention is not limited to the specific technical solutions described in the above embodiments. All technical solutions formed by equivalent substitutions are within the scope of protection claimed by the present invention.

Claims

1. A ferrous ion-modified Ti2CT x The preparation method of carrageenan-polyacrylamide composite hydrogel material is characterized by: The steps include the following: (1) Carrageenan, acrylamide, N,N′-methylenebisacrylamide and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone were dispersed and dissolved in deionized water, and heated and stirred until the solid was completely dissolved to obtain a carrageenan-polyacrylamide (CA-PAM) hydrogel prepolymer. (2) Titanium carbide Ti2CT x The aqueous solution of nanosheets was added to the carrageenan-polyacrylamide hydrogel prepolymer solution prepared in step (1), and stirred until Ti2CT was reached. x The aqueous solution was mixed evenly with the carrageenan-polyacrylamide hydrogel prepolymer to obtain Ti2CT. x / Carrageenan-polyacrylamide (Ti2CT) x / CA-PAM) composite hydrogel prepolymer; (3) Transfer the composite hydrogel prepolymer obtained in step (2) into a petri dish and refrigerate it at 4°C until it solidifies; (4) Ti2CT was prepared by irradiating the solid obtained in step (3) with ultraviolet light. x / Carrageenan-polyacrylamide composite hydrogel; (5) The Ti2CT obtained in step (4) x Ferrous-modified Ti2CT was prepared by immersing carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferrous chloride solution. x / Carrageenan-Polyacrylamide Fe 2+ / Ti2CT x / CA-PAM composite hydrogel material.

2. The ferrous ion-modified Ti2CT according to claim 1 x The preparation method of carrageenan-polyacrylamide composite hydrogel material is characterized by: : In step (1), the mass ratio of carrageenan, acrylamide, N,N′-methylenebisacrylamide and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone is 80.2:16.05:3.6:0.15, the stirring speed is 1000 rpm, the heating temperature is 95℃, and the heating time is 2h. In step (2), Ti2CT x The aqueous solution concentration was 15 mg / mL, the volume ratio of the aqueous solution to the hydrogel prepolymer was 9:1, the stirring speed was 1000 rpm, and the stirring time was 10 min. In step (4), the wavelength of the ultraviolet lamp is 365nm and the illumination time is 1h; In step (5), the concentration of ferrous chloride is 4 mol / L and the soaking time is 2 h.

3. The ferrous ion-modified Ti2CT according to claim 1 x The preparation method of carrageenan-polyacrylamide composite hydrogel material is characterized by: : (1) Mix 0.6g LiF with 6mL hydrochloric acid until homogeneous, then add 0.2g of commercial transition metal carbonitride Ti2AlC. Stir the mixture at 40℃ for 24h. Centrifuge the product to obtain a precipitate. The precipitate was dispersed in deionized water (O2 removed) and repeatedly shaken and washed until the pH of the dispersion was between 6 and 7; this yielded Ti2CT with a relatively thin lamellar structure. x Nanosheets; (2) Add 1.12g of carrageenan, 0.224g of acrylamide, 0.002g of N,N′-methylenebisacrylamide and 0.05g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylphenylacetone to 45mL of deionized water and stir at 1000rpm and 95℃ for 2 hours. Then add 5mL of Ti2CT from step (1) with a concentration of 15mg / mL. x An aqueous solution of nanosheets was added to the above mixed solution, and the mixture was stirred at 1000 rpm for 10 minutes to obtain Ti2CT. x A prepolymer solution for carrageenan-polyacrylamide composite hydrogel was prepared; after storing the petri dish containing the prepolymer solution at 4°C for one hour, the sample was irradiated with ultraviolet light for one hour to obtain Ti2CT. x / Carrageenan-polyacrylamide composite hydrogel; (3) The Ti2CT in step (2) x After immersing the carrageenan-polyacrylamide composite hydrogel in a 4 mol / L ferrous chloride solution for 2 hours, ferrous ion-modified Ti2CT can be obtained. x / Carrageenan-polyacrylamide composite hydrogel.

4. Ferrous ion modified Ti2CT according to any one of claims 1-3 x A composite hydrogel prepared by a method for preparing carrageenan-polyacrylamide composite hydrogels.

5. The ferrous ion-modified Ti2CT according to claim 4 x A method for preparing flexible sensors using carrageenan-polyacrylamide composite hydrogels, characterized in that... : Using spin coating, the prepared Ti2CT x A prepolymer solution of carrageenan-polyacrylamide composite hydrogel was spin-coated onto a flexible interdigital electrode. Except for the two exposed electrodes, the rest of the electrode was covered by the prepolymer solution. The flexible interdigital electrode coated with the prepolymer solution was stored at 4°C for 20 minutes, then irradiated with ultraviolet light for 20 minutes, and finally immersed in a 4M FeCl2 solution for 10 minutes to obtain a flexible temperature sensor.

6. Ferrous ion-modified Ti2CT prepared according to claim 5 x Flexible sensor prepared from carrageenan-polyacrylamide composite hydrogel.

7. The flexible sensor according to claim 6 is used for temperature detection.

8. The flexible sensor according to claim 6 is used for temperature detection, characterized in that... The two electrodes of the flexible temperature sensor are connected to the data acquisition unit via wires. The flexible temperature sensor is placed on a semiconductor hot and cold stage, and the data acquisition unit records the temperature sensor's response to temperature changes.

9. The flexible sensor according to claim 6 is used for temperature detection, characterized in that... It can be used to detect human body temperature.

Citation Information

Patent Citations

  • Stretchable humidity sensor with thin film structure and manufacturing method and application thereof

    CN113237924A

  • Application of conductive hydrogel based on polyacrylamide-carrageenan in flexible oxygen sensor

    CN113929818A